Flipped Materials of Wetland Texts for English Teaching at Faculty of Teacher Training and Education, Lambung Mangkurat University - Arapah, Elvina; Arini, Dini Noor (Universitas Islam Negeri Raden Intan Lampung, 2021)
Although smartphones were not prohibited in the campus environment in Era 4.0, smartphones were still limited in their use as a means of communication and connection. Supposedly, the use of this smartphone must of course be observed wisely and maximized by various related parties, for example by making it a medium for learning. The challenge faced in maximizing the use of smartphones for learning is the limitations in processing and or managing existing material. With the various backgrounds and reasons outlined above, the study tries to develop Flipped Materials for English Courses at the Faculty of Teacher Training and Education, Lambung Mangkurat University. This research uses research and development type for Flipped Material on Wetlands in digital form which is developed and tested for its feasibility in a limited scope. For this research, the study took samples with consideration of feasibility in reaching the subjects. Sampling is done by using the Cluster Random Technique because the characteristics of the population used as the research subject are considered to be the same, namely students of ULM semester I.Although smartphones were not prohibited in the campus environment in Era 4.0, smartphones were still limited in their use as a means of communication and connection. Supposedly, the use of this smartphone must of course be observed wisely and maximized by various related parties, for example by making it a medium for learning. The challenge faced in maximizing the use of smartphones for learning is the limitations in processing and or managing existing material. With the various backgrounds and reasons outlined above, the study tries to develop Flipped Materials for English Courses at the Faculty of Teacher Training and Education, Lambung Mangkurat University. This research uses research and development type for Flipped Material on Wetlands in digital form which is developed and tested for its feasibility in a limited scope. For this research, the study took samples with consideration of feasibility in reaching the subjects. Sampling is done by using the Cluster Random Technique because the characteristics of the population used as the research subject are considered to be the same, namely students of ULM semester I.